Defining inflammatory musculoskeletal manifestations in systemic lupus erythematosus. (27th September 2018) - Zayat, Ahmed S; Mahmoud, Khaled; Md Yusof, Md Yuzaiful; Mukherjee, Sandeep; D'Agostino, Maria-Antoinetta; Hensor, Elizabeth M A; Wakefield, Richard J; Conaghan, Philip G; Edwards, Christopher J; Emery, Paul; Vital, Edward M
Abstract: Objective: To define the prevalence and clinical associations of clinical and imaging definitions of synovitis in unselected SLE patients with musculoskeletal (MSK) symptoms. Methods: 112 patients with SLE (excluding RF and CCP positive patients); 88 consecutive with inflammatory MSK symptoms and 24 asymptomatic SLE controls were recruited. Patients had clinical assessment (BILAG, SLEDAI, joint counts, patient and physician visual analogue score), routine laboratory tests and US of two hands and wrists (synovitis and tenosynovitis, OMERACT definitions). Results: Overall, 68% (60/88) of symptomatic patients had US inflammation (grey scale ⩾ 2 and/or PD ⩾ 1 or tenosynovitis) compared with 17% (4/23) of asymptomatic patients. In symptomatic patients, clinical inflammation was seen defined by BILAG A or B in 38% (34/88) or defined by the SLEDAI-MSK criterion in 32% (28/88). BILAG A/B had sensitivity (95% CI) of 56% (41, 69%) and specificity of 89% (72, 96%) for US-confirmed inflammation. SLEDAI-MSK criterion had sensitivity of 44% (31, 59%) and specificity of 89% (72, 96%). In patients with inflammatory symptoms, 27% (24/88) had subclinical inflammation (abnormal US but no clinically swollen joints) and 35% (31/88) had no clinical or US inflammation. Subclinical tenosynovitis and PD were associated with significantly higher IgG, physician visual analogue score, tender joint count. Conclusion: In SLE patients with MSK symptoms, a large proportion of objective, clinically meaningful inflammation is only identifiable by US. The existing classification of MSK SLE using disease activity instruments based on joint swelling is inaccurate to guide patient selection for clinical trials, biologic therapy, or treat-to-target protocols.